Information Retrieval Technology: 5th Asia Information Retrieval Symposium, AIRS 2009, Sapporo, Japan, October 21-23, 2009 : Proceedings - Lee, Gary Geunbae; Song, Dawei; Lin, Chin-Yew; Aizawa, Akiko; Kuriyama, Kazuko; Yoshioka, Masaharu; Sakai, Tetsuya (Springer, 2009)
This book constitutes the refereed proceedings of the 5th Asia Information Retrieval Symposium, AIRS 2009, held in Sapporo, Japan, in October 2009. The 18 revised full papers and 20 revised poster papers presented were carefully reviewed and selected from 82 submissions. All current aspects of information retrieval - in theory and practice - are addressed; working with text, audio, image, video and multimedia data.